2022
DOI: 10.1002/essoar.10512709.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breaking the Ring of Fire: How ridge collision, slab age, and convergence rate narrowed and terminated the Antarctic continental arc

Abstract: The geometry of the Antarctic-Phoenix Plate system, with the Antarctic Plate forming both the overriding plate and the conjugate to the subducting oceanic plate, allows quantification of slab age and convergence rate back to the Paleocene and direct comparison with the associated magmatic arc. New Ar-Ar data from Cape Melville (South Shetland Islands, SSI) and collated geochronology shows Antarctic arc magmatism ceased at ˜19 Ma. Since the Cretaceous, the arc front remained ˜100 km from the trench whilst its r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…We suggest that this event may be related to the end of the arc magmatism of this region. Furthermore, recently, Burton-Johnson et al (2022) modelled the waning of the subduction and suggested that most of the Cenozoic magmatism in the Antarctic Peninsula is associated with the progressively younging age of the Phoenix Plate, which is subducted underneath the Antarctic Peninsula. Additionally, this process may have evolved into the development of the Bransfield Strait, a Pliocene marginal back-arc (e.g., Barker, 1982).…”
Section: Migration Of Volcanismmentioning
confidence: 99%
“…We suggest that this event may be related to the end of the arc magmatism of this region. Furthermore, recently, Burton-Johnson et al (2022) modelled the waning of the subduction and suggested that most of the Cenozoic magmatism in the Antarctic Peninsula is associated with the progressively younging age of the Phoenix Plate, which is subducted underneath the Antarctic Peninsula. Additionally, this process may have evolved into the development of the Bransfield Strait, a Pliocene marginal back-arc (e.g., Barker, 1982).…”
Section: Migration Of Volcanismmentioning
confidence: 99%